Integrating English Language Communication Skills into Disciplinary Curricula : Options and Strategies : Final Report. - Arkoudis, Sophie (Office for Learning and Teaching, 2014)
Final report of a Teaching Fellowship at The University of Melbourne. Australian universities state that communication skills are important graduate attributes. Yet there are perceptions within the community that graduates lack the necessary communication skills for employability. This Fellowship explored the gap between what universities espouse and community perceptions of graduates' oral and written communication skills. The research focused on effective and economical ways of addressing the gap. The resources developed from the Fellowship have been designed to assist universities to strengthen their reputations regarding the English language standards of their graduates.